Female stress urinary incontinence MDT. (July 2019) - Sihra, Néha; Kujawa, Magda; Solomon, Eskinder; Harding, Chris; Sahai, Arun; Malde, Sachin
The management of female stress urinary incontinence (SUI) has come under scrutiny in recent years following growing reports of mesh-related complications. Patients require thorough evaluation and management as part of a multidisciplinary team, and extensive counselling about the surgical treatment options is imperative. There is no clear consensus on the optimal management of the complex group of patients with mesh-related complications or recurrent SUI. We present two cases of female SUI to highlight the key factors to be considered when managing these patients. Level of evidence: Level 5.